Investigating the effect of thermal treatment on nutritional properties of Kelulut Honey - Razali, Muhammad Faiz; Amri, Muhammad Akmal; Mohamed, Elizah; Othman, Zolkanain; Mohd Fauzi, Noor Akhmazillah (2024)
The natural antioxidants flavonoids and phenolic acids make Kelulut honey a healthy alternative, but heating it over 90 degrees Celsius can cause it to lose some of its flavour and nutritional value. The aim of this study was to investigate how thermal treatment affects the antioxidant activity, total phenolic content (TPC), and brown pigment production of Kelulut honey. The samples were heated at three different temperatures (50, 60, and 70 degrees Celsius) for various durations (5, 10, 15, and 30 minutes). Antioxidant activity and TPC were assessed using the DPPH radical scavenging method and the Folin-Ciocalteau reagent, respectively. The findings revealed that the honey heated to 70 degrees Celsius for 15 minutes had the highest antioxidant activity compared to the unheated honey. The TPC was at its peak after 5 minutes of heating at 50 degrees Celsius, but it decreased significantly after 30 minutes. The optimal nutritional value of honey was achieved by treating it at 70 degrees Celsius for 15 minutes. Fourier transform infrared spectroscopy was used to identify the phenolic compounds, and the IR spectra peaks were found to be located in the hydroxyl group (-OH) in all samples. Therefore, it can be inferred that Kelulut honey's nutritional value was not impaired by thermal treatment at 50-70 degrees Celsius for 5-30 minutes